Alpha-lipoic acid protects against hepatic ischemia-reperfusion injury in rats - DULUNDU, ENDER; ERCAN, FERİHA; ŞENER, GÖKSEL (KARGER, 2007)
Background and Aim: To evaluate the protective effect of alpha-lipoic acid in reducing oxidative damage after severe hepatic ischemia/reperfusion (IR) injury. Methods: Wistar albino rats were subjected to 45 min of hepatic ischemia, followed by 60 min reperfusion period. Lipoic acid (100 mg/kg i.p.) was administered 15 min prior to ischemia and immediately before reperfusion period. At the end of the reperfusion period aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) activity, and cytokine, TNF-alpha and IL-1 beta levels were determined in serum samples. Malondialdehyde (MDA), and glutathione (GSH) levels and myeloperoxidase (MPO) activity were determined in the liver tissue samples while formation of reactive oxygen species was monitored by using chemiluminescence ( CL) technique with luminol and lucigenin probes. Tissues were also analyzed histologically. Results: Serum ALT, AST, and LDH activities and TNF-alpha and IL-1 beta levels were elevated in the I/R group, while this increase was significantly lower in the group of animals treated concomitantly with lipoic acid. Hepatic GSH levels, significantly depressed by I/R, were elevated back to control levels in lipoic acid-treated I/R group. Furthermore, increases in tissue luminol and lucigen-in CL, MDA levels and MPO activity due to I/R injury were reduced back to control levels with lipoic acid treatment. Conclusion: Since lipoic acid administration alleviated the I/R-induced liver injury and improved the hepatic structure and function, it seems likely that lipoic acid with its antioxidant and oxidant-scavenging properties may be of potential therapeutic value in protecting the liver against oxidative injury due to ischemia-reperfusion. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: ischemia/reperfusion; lipoic acid; cytokine; lipid peroxidation; myeloperoxidase; REACTIVE OXYGEN; DIHYDROLIPOIC ACID; FREE-RADICALS; LIVER-INJURY; AGED RATS; ANTIOXIDANT; MECHANISMS; MELATONIN; MYELOPEROXIDASE; INFLAMMATION